Targeted next-generation sequencing of locally advanced squamous cell carcinomas of the head and neck reveals druggable targets for improving adjuvant chemoradiation - Tinhofer, Ingeborg; Budach, V.; Saki, M.; Konschak, R.; Niehr, F.; Jöhrens, K.; Weichert, Wilko; Linge, A.; Lohaus, F.; Krause, M.; Neumann, K.; Endris, Volker; et al. (European journal of cancer, 2016)
Background - Despite clear differences in clinical presentation and outcome, squamous cell carcinomas of the head and neck (SCCHN) arising from human papilloma virus (HPV) infection or heavy tobacco/alcohol consumption are treated equally. Next-generation sequencing is expected to reveal novel targets for more individualised treatment. - Patients and methods - Tumour specimens from 208 patients with locally advanced squamous cell carcinoma of the hypopharynx, oropharynx or oral cavity, all uniformly treated with adjuvant cisplatin-based chemoradiation, were included. A customised panel covering 211 exons from 45 genes frequently altered in SCCHN was used for detection of non-synonymous point and frameshift mutations. Mutations were correlated with HPV status and treatment outcome. - Results - Mutational profiles and HPV status were successfully established for 179 cases. HPV- tumours showed an increased frequency of alterations in tumour suppressor genes compared to HPV+ cases (TP53 67% versus 4%, CDKN2A 18% versus 0%). Conversely, HPV+ carcinomas were enriched for activating mutations in driver genes compared to HPV- cases (PIK3CA 30% versus 12%, KRAS 6% versus 1%, and NRAS 4% versus 0%). Hotspot TP53 missense mutations in HPV- carcinomas correlated with an increased risk of locoregional recurrence (hazard ratio [HR] 4.3, 95% confidence interval [CI] 1.5-12.1, P=0.006) and death (HR 2.2, 95% CI 1.1-4.4, P=0.021). In HPV+ SCCHN, driver gene mutations were associated per trend with a higher risk of death (HR 3.9, 95% CI 0.7-21.1, P=0.11). - Conclusions - Distinct mutation profiles in HPV- and HPV+ SCCHN identify subgroups with poor outcome after adjuvant chemoradiation. Mutant p53 and the phosphoinositide 3-kinase pathway were identified as potential druggable targets for subgroup-specific treatment optimisation.